Distribution of Trace Metals in Vertebrate and Invertebrate Species from Ubeji Creek, Southern Nigeria - Ndinwa, G.C.C; Peretomode, M; Asiagbe, T (International Journal of Advances in Life Science and Technology, 2014)
Trace metals content in water, fishes (Tilapia mariae, Clarias gariepinus), earthworm (Libydrius violaceous) and sediment were determined from Ubeji River using Atomic Absorption Spectrophotometer (AAS). Metals determined were lead, cadmium, zinc, mercury, arsenic, copper and Iron. The results obtained revealed that all the metals were detected. Also, there were variations in metal levels in the samples. Highest Zn level was obtained in all the samples analysed (0.284ppm and 0.284ppm in water, 24.0mg/kg in Clarias gariepinus, 28.8mg/kg in Tilapia mariae, 1.16mg/kg in earthworm and 0.64mg/kg in sediment). The concentrations of trace metals obtained in this study are found to be dangerous. The metal levels in water from Ubeji River are higher than the WHO/FEPA standards for water quality. The concentrations of lead, zinc and copper obtained in the whole body of fishes exceeded the WHO/FEPA set standards for aquatic life. The presence of trace metals found in the sample from Ubeji River is attributed to the proximity of petroleum activity, construction works and other allied companies.